If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + y = -3 Solving 12x + y = -3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1y' to each side of the equation. 12x + y + -1y = -3 + -1y Combine like terms: y + -1y = 0 12x + 0 = -3 + -1y 12x = -3 + -1y Divide each side by '12'. x = -0.25 + -0.08333333333y Simplifying x = -0.25 + -0.08333333333y
| 2b^2+5b-63=0 | | 261=79-x | | 1/x-1/x+1=1/x(2)+x | | 27-6z=-5(7z-9) | | X*2X=166 | | -16=4y-9 | | 2(8b+2)-1+4g-(2-5g)= | | -x-7=x+1 | | x=160-(170-x) | | 43=3u-11 | | x^3-12x^2-6x-12=0 | | 33b-23=b | | 29-5x=9-7x | | 12A-7=-1 | | y=0.15x+0.15 | | 7-4a=2a+2-5a | | 12=6-2y | | y-1=1/5(x-3) | | solvingx^3-12x^2-6x-12=0 | | -7-x=1+x | | -(7-7a)+4a=-23+3a | | 20x^2(-3+4x)=0 | | 1/3x-5/6x=17 | | 157=11-w | | 21x+42=-3 | | 2b^2+5b-62=0 | | 4x-11=3x+3 | | 7-g=-11 | | Y=5/2-20 | | 17j-13j=16 | | 6x+8y=480 | | 2-(6x-19)=7(x-2) |